Spatial Planning Implementation Effectiveness: Review and Research Prospects - Guan Li; Liping Wang; Cifang Wu; Zhongguo Xu; Yuefei Zhuo; Xiaoqiang Shen (Land, 2022)
The question of how to implement spatial planning more effective is a fundamental but very difficult one and one that has been of great interest to both the academic and practical community. However, a comprehensive review of the conceptual models and methodological systems for evaluating spatial planning implementation, and the existing practical research results of various types of spatial planning implementation evaluation, are yet to be presented. The study systematically reviews the main research findings in the field of spatial planning implementation from four aspects: conceptual analysis, measurement methods, evaluation frameworks and evaluation methods. This study found three distinct evolutionary features of research in this field: (1) The evaluation concept changes from complete rationality to limited rationality; (2) research methodology changes from a simple closed system to a complex open system; (3) the research perspective shifts from the map to the main body of planning implementation behavior. It is suggested that an important part of future research lies in establishing a system for evaluating the effectiveness based on a single subject who is an actor in the planning implementation process. On this basis, the micro-influencing mechanisms of planning implementation effects will then be explored. Deepening the research to the individual level will help improve planning implementation’s effectiveness.